Interactome of Glyceraldehyde-3-Phosphate Dehydrogenase Points to the Existence of Metabolons in Paracoccidioides lutzii - e Silva, Kleber Santiago Freitas; Lima, Raisa Melo; Baeza, Lilian Cristiane; Lima, Patrícia de Sousa; Cordeiro, Thuany de Moura; Charneau, Sébastien; da Silva, Roosevelt Alves; Soares, Célia Maria de Almeida; Pereira, Maristela (Frontiers in Microbiology, 2019)
Paracoccidioides is a dimorphic fungus, the causative agent of paracoccidioidomycosis. The disease is endemic within Latin America and prevalent in Brazil. The treatment is based on azoles, sulfonamides and amphotericin B. The seeking for new treatment approaches is a real necessity for neglected infections. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is an essential glycolytic enzyme, well known for its multitude of functions within cells, therefore categorized as a moonlight protein. To our knowledge, this is the first approach performed on the Paracoccidioides genus regarding the description of PPIs having GAPDH as a target. Here, we show an overview of experimental GAPDH interactome in different phases of Paracoccidioides lutzii and an in silico analysis of 18 proteins partners. GAPDH interacted with 207 proteins in P. lutzii. Several proteins bound to GAPDH in mycelium, transition and yeast phases are common to important pathways such as glycolysis and TCA. We performed a co-immunoprecipitation assay to validate the complex formed by GAPDH with triose phosphate isomerase, enolase, isocitrate lyase and 2-methylcitrate synthase. We found GAPDH participating in complexes with proteins of specific pathways, indicating the existence of a glycolytic and a TCA metabolon in P. lutzii. GAPDH interacted with several proteins that undergoes regulation by nitrosylation. In addition, we modeled the GAPDH 3-D structure, performed molecular dynamics and molecular docking in order to identify the interacting interface between GAPDH and the interacting proteins. Despite the large number of interacting proteins, GAPDH has only four main regions of contact with interacting proteins, reflecting its ancestrality and conservation over evolution.